Effect of thermal annealing on dielectric property and thermal conductivity of Si3N4–BaTiO3 composite ceramics. Issue 5 (1st March 2022) - Zhang, Chunyan; Wang, Hongwei; Fang, Haolan; Meng, Fancheng; Lin, Huixing
Abstract: Si3 N4 –BaTiO3 composite ceramics were prepared by hot pressing sintering. The effects of the amount of BaTiO3 and annealing process on the microstructure, phase composition, dielectric properties and thermal conductivity of Si3 N4 composite ceramics were studied. With the increase of BaTiO3 content, the density and the dielectric performance of the Si3 N4 -based composite ceramics are improved, while the thermal conductivity is reduced. The annealing treatment can not only inhibit the growth of β-Si3 N4, refine the grain, reduce the content of intercrystalline glass phase and porosity, but also promote the precipitation of hexagonal barium titanate, all of which are beneficial to increase the dielectric constant and decrease the dielectric loss, but will slightly reduce the thermal conductivity of Si3 N4 –BaTiO3 composite ceramic. The sample A2BT15 with 15% BaTiO3 sintered at 1750 °C for 2 h and annealed at 1300 °C exhibited the maximum dielectric constant (ε = 10.57), the minimum dielectric loss (tanδ = 9×10 -4 ), a high relative density (98.8%) and an acceptable thermal conductivity (14.5 W·m -1 ·K -1 ). Therefore, the selection of appropriate BaTiO3 content and annealing process can regulate the dielectric property, thermal performance and mechanical property of Si3 N4 –BaTiO3 composite ceramics in a certain range.